A New Hybrid Active Vibration Control System for Suppressing Spacecraft Microvibration With Broadband Random Vibration and Multiharmonics Vibration - Zhang, Qian; Liu, Jinxin; Wang, Chenxi; Zhao, Yuting; Xu, Maojun; Liu, Naijin; Chen, Xuefeng (IEEE transactions on instrumentation and measurement, 2025)
High-precision in-orbit missions, such as deep space exploration, communication, and Earth observation, have raised higher requirements for spacecraft microvibration suppression (MVS). The complex microvibration environment on spacecraft results in microvibration signals appearing as a combination of broadband random vibration and multiharmonic vibration, posing challenges to MVS. In this article, a new Volterra filtering-based hybrid active vibration control (NVHAVC) system is proposed for suppressing complex microvibrations in spacecraft. In the proposed NVHAVC system, a modified generalized soft-root-sign (MGSRS) adaptive algorithm is used to replace the least-mean-square adaptive algorithm in the filtered-x adaptive controller to address the impact of non-Gaussian or impulse noise on the MVS performance. And the MGSRS and Volterra filtering are introduced into both the broadband subsystem and narrowband subsystem for improving the MVS performance. Meanwhile, a frequency estimation algorithm based on an extended Kalman filter (EKF) is also introduced into the narrowband subsystem to improve the MVS performance of multiharmonic vibration with unknown time-varying frequency and amplitude. In addition, the physical output of the narrowband subsystem is reconstructed in the NVHAVC system framework to reduce the decrease of MVS performance caused by the same error feedback in both the broadband subsystem and the narrowband subsystem of the traditional hybrid active vibration control (AVC) system. Numerical simulation and experimental verification are conducted to validate the effectiveness of the proposed NVHAVC system. The results show that the improved broadband and narrowband subsystems can realize the MVS performance improvements of approximately 5-8 dB and 24-26 dB, respectively, compared with the traditional broadband and narrowband subsystems. The proposed NVHAVC system can achieve microvibration performance improvement of approximately 10 dB compared with the traditional hybrid AVC (HAVC) system.